2003
DOI: 10.1016/s0896-6273(03)00476-8
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical LTD via Coincident Activation of Presynaptic NMDA and Cannabinoid Receptors

Abstract: There is a consensus that NMDA receptors (NMDARs) detect coincident pre- and postsynaptic activity during induction of long-term potentiation (LTP), but their role in timing-dependent long-term depression (tLTD) is unclear. We examine tLTD in neocortical layer 5 (L5) pyramidal pairs and find that tLTD is expressed presynaptically, implying retrograde signaling. CB1 agonists produce depression that mimics and occludes tLTD. This agonist-induced LTD requires presynaptic activity and NMDAR activation, but not pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

60
717
10
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(789 citation statements)
references
References 81 publications
60
717
10
2
Order By: Relevance
“…The role of endocannabinoids in cerebellar plasticity Endocannabinoid receptor-dependent forms of presynaptic LTD exist outside the cerebellum [10,17,35,40], and endocannabinoids are well-described in mediating shortterm plasticity in the cerebellum [6,7,22]. In contrast to the form of LTD described in this study, these CB1 The role of endocannabinoids in PF long-term plasticity had been less clear.…”
Section: Demonstration Of Preltdmentioning
confidence: 56%
“…The role of endocannabinoids in cerebellar plasticity Endocannabinoid receptor-dependent forms of presynaptic LTD exist outside the cerebellum [10,17,35,40], and endocannabinoids are well-described in mediating shortterm plasticity in the cerebellum [6,7,22]. In contrast to the form of LTD described in this study, these CB1 The role of endocannabinoids in PF long-term plasticity had been less clear.…”
Section: Demonstration Of Preltdmentioning
confidence: 56%
“…In view of the results on LTD in layer--V neocortical neurons 44 , this trace could be related to endocannabinoids released from the postsynaptic site. Coincidence of this slow trace with the activation of presynaptic NMDA receptors (which rapidly respond to the glutamate released by presynaptic activity x(t)) could be the trigger signal for LTD 44 . Indeed, the duration of the LTD part in the STDP function increases, if the endocannabinoid trace is artificially prolonged (see Fig 9 of 44 ).…”
Section: Discussionmentioning
confidence: 91%
“…Coincidence of this slow trace with the activation of presynaptic NMDA receptors (which rapidly respond to the glutamate released by presynaptic activity x(t)) could be the trigger signal for LTD 44 . Indeed, the duration of the LTD part in the STDP function increases, if the endocannabinoid trace is artificially prolonged (see Fig 9 of 44 ). In other neuron types and brain areas, the same mathematical model (but with different parameters) could correspond to different biophysical mechanisms of LTD. For example, in hippocampal CA1 neurons, the trace --could reflect the calcium entry through voltage--gated ion channels during depolarization which, when combined with synaptic signals (caused by the presynaptic spike arrival x), would give rise to calcium signals necessary to trigger LTD (reviewed in 19--20,44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have demonstrated that the Calcium control hypothesis does not hold true for excitatory synapses between cortical pyramidal cells -at which there is no evidence for the existence of a triphasic STDP rule. A variety of alternative mechanisms, including metabotropic glutamate receptor, pre-synaptic NMDAr and retrograde endocannabinoid signalling, have been implicated in the induction of LTD by spike-timing stimulation protocols in cortex [77][78][79][80]. It seems likely that this dichotomy in synaptic plasticity mechanisms between cortex and hippocampus might both reflect and be reflected by functional differences in neural processing mediated by these regions.…”
Section: Discussionmentioning
confidence: 99%